Prenatally diagnosed patent urachus with umbilical cord cyst and early surgical intervention - Blažík, R; Matěcha, J; Pýchová, M; Bayerová, E; Chmel, R; Černý, M; Fait, T (Ceska gynekologie, 2019)
OBJECTIVE: Description of rare diagnosis of patent urachus. DESIGN: Case report. SETTING: Department of Obstetrics and Gynecology, 2nd Faculty of Medicine and Faculty Hospital Motol Prague. CASE REPORT: Patent urachus is a rare diagnosis, which in this case was detected prenatally by ultrasound. Involution of the urachus is not fully completed upon birth, therefore in cases of small persisting communication between the urinary bladder and the umbilicus conservative approach and waiting for spontaneous closure is usually chosen. In our case surgery treatment has chosen as a prevention of urinary infection because of patent urachus manifested as a wide communication. CONCLUSION: This congenital defect usually manifests itself early after birth as a visible structural anomaly of the umbilicus and/or as urine leakage in the umbilicus opening area. It is important to keep in mind that urachus irregularities may be accompanied by other urinary system defects. Every child presenting with such an anomaly should therefore be thoroughly examined. If the procedure is performed by an experienced surgical team postoperative complications are uncommon and overall long-term prognosis for patients is excellent.
Keywords: Urachal Cyst; pupečník; Female; dítě; Urinary Bladder; umbilical cord cyst; těhotenství; močový měchýř; Rare Diseases; ultrasonografie prenatální; patent urachus; vzácné nemoci; ženské pohlaví; Child; urachus; Pregnancy; Ultrasonography, Prenatal; Umbilical Cord; cysta urachu; Urachus; lidé; Humans